BERBAGAI JENIS PUPUK KOMPOS DAN NPK 16:16:16 UNTUK MENINGKATKAN PRODUKSI TANAMAN KACANG PANJANG - Roslianti, Meli; Susanti, Sari; Irwansyah, Chusrin; Lukmanasari, Putri (Jurnal Agroteknologi, 2025)
The demand for long bean plants is still quite high among the public, but the production of long bean plants is decreasing every year. This research aims to determine the growth and production of long bean plants when given various types of compost and NPK Mutiara 16:16:16. This research used a Completely Randomized Design (CRD) of 2 factors, the first factor was Providing Various Types of Compost Fertilizer (corn litter, banana peels, cassava peels and pineapple peels) and the second factor was NPK Mutiara 16:16:16 (0 kg/ha, 100 kg/ha, 200 kg/ha, 300 kg/ha). The variables observed were Net Assimilation Rate, Relative Growth Rate, flowering age, harvest age, number of pods, pod weight and pod length per plant. The results of the research showed that the combination of pineapple peel compost and NPK Mutiara 16:16:16 could increase the growth and production of long bean plants compared to other treatments. Providing compost or NPK Mutiara 16:16:16 fertilizer alone does not improve all observed parameters on the growth and production of long bean plants.